PPTTG PENERAPAN INSTALASI PENGOLAHAN BERSIH MENGGUNAKAN SISTEM FILTRASI BERTINGKAT - Leila kalsum; Abu Hasan; Arfan Hasan (Politeknik Negeri Sriwijaya, 2019)
Application of technology to the community program is intended to help solve the problem of clean water that exists in SMP Negeri 3 and SMP PPT in Kenten Laut, Talang Kelapa District, Banyuasin. Before this program was held, the condition of the water used by the school was quite apprehensive because it only utilized the water available in the swamps and rivers around the school. The available water has poor characteristics, especially containing turbidity and iron that have not yet met the standard. Considering such conditions, we apply the results of our research to be able to assist these two schools in providing clean water through the Application of Water Treatment Plants. This installation is quite simple and easy to operate, where the installation consists of several main process such as netralitation, coagulation, floculation, sedimentation, and stage of filtration. The quality of clean water product from the installation has fulfill the requirements as a source of clean water based on Permenkes RI No.492 / Menkes / Per / IV / 2010.